A retrospective evaluation of eastern coral snake envenomation and antivenom administration in cats: 30 cases (2012–2019). (February 2021) - Maxwell, Kathleen; Fraser, Brittney; Schaer, Michael; Allen, Ashley
Abstract: Thirty cats were identified to be have been suspected to have a potential coral snake envenomation after searching medical records from 2012 to 2019 at a university teaching hospital. The records were reviewed and evaluated for signalment, date and time of the snake encounter, elapsed time between encounter and hospital examination, presenting complaint, initial physical examination findings, initial laboratory findings, antivenom dose and duration of administration, adverse reactions to antivenom, additional treatments administered, progression of clinical signs, length of hospitalization, and outcome. Thirteen cats presented with clinical signs consistent with envenomation while 17 cats were treated for possible asymptomatic envenomation, as defined by the owner discovering a live or dead coral snake in their home or on their property. Initial physical examination findings included tachypnea with short shallow breaths and use of accessory muscles; tetraparesis with normal or decreased to absent spinal reflexes; cranial nerve deficits including decreased to absent gag, slow pupillary light reflexes, and absent physiologic nystagmus; and normal or altered mentation. Laboratory findings included hypercapnia, hyperglycemia, hypokalemia, increased aspartate aminotransferase activity, increased alanine aminotransferase activity, echinocytosis, leukocytosis, azotemia, and hyperlactatemia. Twenty-eight cats received antivenom; two cats received two vials while twenty-six cats received one vial. Antivenom reaction was suspected in one cat that developed facial swelling during administration of the drug. Average length of hospitalization was 1 day for cats without clinical signs and 3 days for cats with clinical signs. Twenty-nine cats survived to discharge. Due to the inclusion criteria of the study, cats euthanized on presentation or discharged without receiving antivenom may have been unintentionally excluded from the study. Diagnosis of eastern coral snake envenomation should be suspected in the cat that has acute onset of lower motor neuron neuropathy. Prognosis with treatment is considered good with 97% of cats surviving to discharge. Antivenom reaction occurred in 3.5% of administrations with none being fatal. Monitoring of hypercapnia was critical in making the decision to mechanically ventilate patients. Supportive care that includes antivenom administration, recumbency care, and mechanical ventilation if needed are the mainstays of therapy. Highlights: The most common clinical signs were tachypnea and tetraparesis. Echinocytosis was noted in 85% of cases where a blood smear was performed. The reaction rate of coral snake antivenom in cats was 3.5%. Prognosis for coral snake envenomation in cats is good to excellent.